STUDY ON DEVELOPMENT OF EFFORT CAPACITY IN NEUROLOCOMOTH DEFICIENCIES - PRODEA, Cosmin; MUREȘAN, Narcisa (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2019)
Physical education and sport are considered to be of major importance in special education, because through its many forms of organization it succeeds in stimulating the positive development of children in special education, both physically and intellectually. In special education, schools have a method that they use in a lively and attractive environment for children, and they seek to form knowledge, skills and understanding to help them integrate into society. The study was conducted over a 4-week period in which we aimed to develop the exercise capacity of subjects by monitoring results from day to day with the help of bracelets that calculate both heartbeat and calorie, distance, and subject trajectory. Last week’s values have seen a big increase compared to the first week, with students having a much higher level of effort. REZUMAT. Studiu privind dezvoltarea capacității de efort la deficienții neurolocomotori. Educația fizică și sportul sunt considerate a fi de importanță majoră în învățământul special, deoarece prin numeroasele sale forme de organizare reușesc să stimuleze dezvoltarea pozitivă a copiilor în învățământul special, fizic și intelectual. În învățământul special, școlile au o metodă pe care o folosesc într-un mediu plin de viață și atractiv pentru copii și caută să formeze cunoștințe, abilități și înțelegere pentru a-i ajuta să se integreze în societate. Studiul a fost realizat pe o perioadă de 4 săptămâni în care ne-am propus să dezvoltăm capacitatea de exercițiu a subiecților prin monitorizarea rezultatelor zilnice cu ajutorul brățărilor care calculează atât ritmul cardiac, cât și caloric, distanța și traiectoria subiectului. Valorile din săptămâna trecută au înregistrat o creștere semnificativă față de prima săptămână, elevii având un nivel mult mai mare de efort. Cuvinte-cheie: educație fizică, frecvență cardiacă, nevoi speciale, învățământ special, brățări cardio, bătăi pe minut.